Caracterização da produção de alface e seleção de genótipos adaptados no município de Itabaiana, Sergipe - Silva, Susi Alves da (2011)
One of the great challenges of agriculture in the State of Sergipe is to characterize the sustainability of production systems, and also offer tools and solutions for the certification of agricultural products. This, the objective was to assess the sustainability of production systems for lettuce farmers of the Itabaiana using the methodology MESMIS (Mark Evaluation Systems of Natural Resource Management Incorporating Sustainability Indicators), testing the indicators regarding their efficiency to assist in decisions making. It was also carried out a selection of lettuce genotypes adapted to climatic conditions of Itabaiana aiming to contribute for sustainability of production systems. In assessing sustainability, the indicators were measured from data obtained from farmers by semi-structured questionnaires, following the steps proposed in the methodology MESMIS. It is concluded that this methodology is effective in assessing the sustainability of farms, and the evaluated systems are not sustainable. As a contribution to sustainability using plant breeding, genotype AFX005B-121-02 was selected as promising to obtain a new cultivar adapted to the conditions of these region with characteristics such as smooth leaves and resistant to nematode Meloidogyne incognita race 1 and to the early flowering, which were identified as weaknesses in production systems, compromising their sustainability.